PENDEKATAN KONSELING REALITA DALAM DUNIA PENDIDIKAN: STUDI LITERATUR - Rachmawati, Ajeng; Purwoko, Budi; Habsy, Bakhrudin All (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
Problems experienced by individuals in the world of education are common. If not handled properly, these problems can develop into stress, anxiety, and even psychological disorders. In this context, teachers and school counselors have an important role and responsibility to help students overcome these problems. One approach that can be used to support individuals in dealing with problems is reality counseling. This approach was developed by William Glasser and focuses on current behavior, without focusing too much on the past. Reality counseling aims to help individuals achieve a successful identity. In the process of achieving this, individuals are driven by various basic needs that motivate their actions to meet these needs. Glasser identified five basic human needs, namely: power, love and belonging, freedom, fun, and survival.